Ekonomik konjonktürün ekonomi haberciliği üzerindeki rolü : ulusal gazetelere yönelik bir inceleme - Söyleyenoğlu, Meltem (My University, 2019)
Türkiye’de 1980’li yıllardan sonra gelişmeye başlayan ekonomi basını, günümüz medyasında, önemli bir uzmanlık alanı haline gelmiştir. Yalnızca yazılı basında değil görsel basında da ekonomi gazeteciliği önemli bir yer tutmaktadır. Türkiye ekonomisinin gelişmesi ve dışa açılması sonucunda ekonomi haberlerine olan talep ve ilgi de artmıştır. Ekonomi basını, hem iş insanlarının hem de vatandaşların ekonomik pozisyon almasında önemli bir referanstır. Bu nedenle ekonomi haberciliğinde kamu yararı ön plandadır. Ancak ülke ekonomileri her zaman gelişim göstermez, krizler ekonomiler için kaçınılmazdır. Ekonomi basını da değişen ekonomik konjonktüre göre yayın politikasında değişiklik yapabilmektedir. Bu çalışma, ekonomi basınının ekonomik konjonktürün kötüye gittiği dönemlerde sergilediği tutumu ortaya koymayı amaçlamaktadır. Bu bağlamda Ağustos 2018’de Türkiye ekonomisinde yaşanan kur dalgalanması ile doların 7 lira, euronun da 8 lirayı aştığı 10-17 Ağustos tarihleri arasında farklı görüşlere sahip dört gazetenin ekonomi haberleri, eleştirel söylem analizine tabi tutularak gazetelerin ekonominin kötü gidişatına karşı izledikleri yayın politikası ortaya konulmaya çalışılmıştır.

Economy press which is started to develop after 1980s in Turkey became an important specialty in modern media. Economic journalism has an important place not only in print press but also in visual press. The demand and interest to economy news are increased due to development of Turkey economy and its openness to foreign countries. The economic press is an important reference in the economic position of both business people and citizens. For this reason, public interest is in the forefront in economic journalism. However, economies of the country do not always develop, crises are inevitable for economies. The economy press is also able to make changes in the publication policy according to the changing economic conjuncture. The aim of this study is to reveal the attitude of the economy press in the period when the economic conjuncture worsens. In this context, the economy news of four newspapers which has different opinions, between the dates of 10-17 August when American Dollar increased to 7 Turkish Lira and Euro increased to 8 Turkish Lira were subjected to critical discourse analysis and publications policies of newspapers related to bad situation of economy were tried to reveal.
Keywords: Basın; basında ekonomi; cyclical fluctuation; economic conjuncture; economics in press; Economy; economy journalism; Ekonomi; Ekonomi basını; ekonomi gazeteciliği; ekonomik konjonktür; exchange rate fluctuation; konjonktürel dalgalanma; kur dalgalanması Economy press; Press